2019
DOI: 10.1101/530352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and feature-selective attention have distinct effects on population-level tuning

Abstract: 1Selective attention is fundamental to cognitive activity and can be deployed in 2 different ways. Non-human primate data suggests that spatial and feature-based 3 visual attention have qualitatively different effects on neural tuning, but this has 4 been challenging to assess in humans. Using multivariate decoding of MEG data, 5we tracked the effects of spatial and feature-selective attention on population-level 6 coding of novel objects. We found that spatial and feature-selective attention 7 interacted mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 90 publications
(140 reference statements)
6
41
2
Order By: Relevance
“…The manipulation of attention showed a strong overall effect with enhanced representation of both the less important direction of approach and the most task-relevant distance to object information for cued dots, regardless of how frequent the targets were (Figure 3). The improved representation of information under attention extends previous findings from us and others (Woolgar et al, 2015b;Goddard et al, 2019;Nastase et al, 2017) to moving displays, in which the participants monitor multiple objects simultaneously.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The manipulation of attention showed a strong overall effect with enhanced representation of both the less important direction of approach and the most task-relevant distance to object information for cued dots, regardless of how frequent the targets were (Figure 3). The improved representation of information under attention extends previous findings from us and others (Woolgar et al, 2015b;Goddard et al, 2019;Nastase et al, 2017) to moving displays, in which the participants monitor multiple objects simultaneously.…”
Section: Discussionsupporting
confidence: 86%
“…The method we used here evaluated the correlation between representational dissimilarity matrices, which has provided high-dimensional information about distance to object, obtained from multiple sensors across the brain areas. This makes the analysis more sensitive to capturing subtle connectivity and also aligns with a major recent shift in literature from univariate to multivariate informational connectivity analyses (Goddard et al, 2016;Goddard et al, 2019;Karimi-Rouzbahani et al, 2019;Karimi-Rouzbahani, 2017;Anzellotti & Coutanche, 2018;Basti et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…Non-human primate research has shown that these regions preferentially code task-relevant information (Rao, Rainer, & Miller, 1997;Freedman et al, 2001;Cromer et al, 2010;Roy et al, 2010;Kadohisa et al, 2013), a result mirrored in human neuroimaging data (Woolgar et al, 2015;Jackson et al, 2017;Jackson & Woolgar, 2018). This selective representation may support preferential coding in other brain regions (Desimone & Duncan, 1995;Miller & Cohen, 2001), as indicated by previous work (Baldauf & Desimone, 2014;Goddard, Carlson, & Woolgar, 2019), yielding a plausible mechanism for a brain-wide focus on relevant information and a key component of cognitive control. For example, Baldauf and Desimone (2014) combined magnetoencephalography and fMRI to show that the inferior frontal junction appears to direct object-based attentional inputs to the inferior-temporal cortex.…”
Section: Discussionsupporting
confidence: 60%
“…We developed a novel connectivity method based on RSA to quantify the relationships between the evolution of information based on perioccipital EEG electrodes and those of the peri-frontal electrodes. As an advantage to previous Granger causality methods (Goddard et al, 2016;Goddard et al, 2019;Karimi-Rouzbahani et al, 2019), the connectivity method developed here allowed us to check whether the transferred signals contained specific aspects of stimulus information.…”
Section: Task Difficulty and Familiarity Level Affect Information Flomentioning
confidence: 99%
“…Timing information is also crucial in evaluating the flows of feed-forward and feedback information as these processes often differ in the temporal dynamics. With the advent of the concept of informational connectivity analysis, we now have the potential to examine the interaction of information between feed-forward and feedback mechanisms to characterize their potential spatiotemporal contribution to familiar face recognition (Goddard et al, 2016;Goddard et al, 2019;Anzellotti and Coutanche, 2018;Basti et al, 2020;Karimi-Rouzbahani et al, 2020). However, this requires novel methods to track the flow of familiarity information from a given brain area to a destination area and link this flow to the behavioural task goals to confirm its biological relevance.…”
Section: Introductionmentioning
confidence: 99%